Pentecostalismo e política: o envolvimento político assembleiano no Amapá - (:unkn) unknown (UNIFAP – Universidade Federal do Amapá, 2016)
The delaicização process of state gave greater freedom for the individual to profess their faith and that other groups could emerge and organize. The twentieth century, specifically in the mid-70s, is marked by religious pluralization, especially with the emergence of Christian spectrum, a period that emphasized greater mobilization of evangelical groups for political and social legitimacy. So Today evangelicals represent a large portion of the Brazilian electorate represented by Pentecostals, neo-Pentecostals, Baptists, Methodists, Presbyterians and others. The legislative and executive the presence of evangelicals linked to Assembly of God is strong, and its significant participation in the Chamber of Deputies and Federal Senate. In Amapaense scenario the Assembly of God denomination is mobilized politically to elect their representatives since the beginning of the 90s, following the evangelical mobilization at national level with the slogan "vote for Brother Brother" aimed elect politicians evangelical segment. It is characterized by the largest Pentecostal evangelical denomination in Amapá (100,821 members according to the IBGE 2010) AD is mobilized politically to elect their peers and ensure their interests. In this context, the present study aims to investigate the support given to political assembleiano of the legislature in Amapá. Desvendo how is the candidate of choice and how it articulates the support of these parliamentarians. To better support the research, analyzed the relationship between religion and politics in Brazil, with attention to the Pentecostal evangelical expansion, especially Assembly of God, that by changing posture, proselytism and political activity resulted in the multiplication of social spaces occupied by that name in Brazilian society, with no differences in Amapá that changed his political stance in an attempt to legitimize itself socially and politically. In the state, AD works from two perspectives both official candidates, and political support. There is a heterogeneity with respect to this support due to its own internal divisions and fragmentations, making AD can not alone elect a candidate from their membership.Through the issue at hand, the theoretical and methodological assumptions of the research focused on qualitative study, where the techniques used are analysis of content, semi-structured interviews and literature review that will serve as a backdrop for understanding the concepts of secularization, religious freedom and participation of evangelicals in Brazil partisan politics.
Keywords: Assembleia de Deus - Amapá; Insurgência pentecostal; Igreja - Política; Pentecostalismo - Brasil; CNPQ::CIENCIAS SOCIAIS APLICADAS